(untitled) (Journal of the College of Languages (JCL), 2022)
Arab translators have always paid great attention to the translation of the Persian literary genres, in particular, contemporary Iranian novels. They have always translated for the most prominent Iranian novelists such as Jalal Al Ahmad, Sadiq Hidayat, Mahmoud Dowlatabadi, Bozorg Alavi, Ismail Fasih‎, Houshang Golshiri, Gholam-Hossein Saedi, Simin Daneshvar, Sadiq Chubak, Samad Behrangi and others that have succeeded in perfectly picturing the Iranian society. Within the perspectives of Arab translators and by using the descriptive - analytical approach, the present study provides an analytical study of the translation into Arabic some of the modern Persian novels. Moreover, the study also gives a critical analysis of the translation of the Egyptian Muhammad Alauddin Mansour into Arabic two of the selected models of the Iranian novels: (Termite) by Bozorg Alavi and (Winter 84) by Ismail Fasih. The study also elucidates a critical analysis of some semantic and stylistic aspects of the translation as well as some of the translator’s committed mistakes between the original and the translated texts. چکیده رمان فارسی یکی از ژانرهای ادبی است که مترجمان عربزبان به آن توجه زیادی نشان دادهاند و میتوان گفت که به ویژه رمانهای معاصر ایرانی همواره مورد اقبال مترجمان عرب بودهاند. و مترجمان عرب بسیاری ازرمانهای نویسندگان مشهور ایرانی را ترجمه کردند که از طریق آنها تصویر جامعه ایران را به جهان عرب منتقل میکردند. در این تحقیق با روش توصیفی - تحلیلی به نقد و بررسی " ترجمهی عربی رمانهای معاصرفارسی" در قالب بررسی موضوعاتی همچون نگاهی به ترجمههای مترجمین عرب از رمانهای معاصر فارسی ، نقدی کوتاه بر ترجمهی رمانهای معاصر فارسی به عربی و نقد وبررسی نمونههای برگزیدهای از ترجمهی مترجم مصری محمد علاء الدین منصور از رمان (موریانه) نوشته بزرگ علوی رمان (زمستان 62) نوشته اسماعیل فصیح پرداختهایم. بدین ترتیب که ضمن مطالعهی دو رمان مذکور و مقابله متن ترجمه شده با متن اصلی ، برخی مسائل معنایی و سبکشناختی و اشتباهات مترجم را با مقایسه متن ترجمه شده با متن اصلی بررسی و تحلیل کردهایم.